Preservation of rumen fluid for the pretreatment of waste paper to improve methane production. (15th March 2019) - Takizawa, Shuhei; Baba, Yasunori; Tada, Chika; Fukuda, Yasuhiro; Nakai, Yutaka
Highlights: Preservation of rumen fluid at 20 °C inhibits the hydrolysis of the waste paper. Preservation at 35 °C increases the loss of organic carbon from rumen fluid. Fibrolytic enzyme activity and protozoa of rumen fluid are retained at 4 °C. Preservation at 4 °C reduces the loss of CO2 production from rumen fluid. Abstract: It is necessary to preserve rumen fluid for transport from slaughterhouses to the pretreatment facilities for use in treating lignocellulosic biomass. In this study, we investigated how the preservation of rumen fluid at various temperatures affects its use in hydrolysis of waste paper. Rumen fluid was preserved anaerobically at 4, 20, and 35 °C for 7 days. The number of protozoa and fibrolytic enzyme activity after preservation at 4 °C were significantly higher than that after preservation at either 20 or 35 °C. Waste paper was subsequently treated with preserved rumen fluid at 37 °C for 48 h. Preservation at 20 °C remarkedly decreased the hydrolysis of waste paper. Xylanase activity in rumen fluid preserved at 35 °C increased during the treatment, which enhanced the solubilization of waste paper as comparable to the control and preservation at 4 °C. Pretreatment of waste paper with rumen fluid preserved at 4 °C showed that the fluid retained high fibrolytic activity, and reduced the loss of organic carbon as substrate for methanogens. Our results suggest that preservation of rumen fluid at 4 °C is most suitable for efficient pretreatment and methane fermentation of waste paper.